Conversation diary in EFL class: A perspective, problem and solution - Syafryadin, Syafryadin (Universitas Muhammadiyah Sidoarjo, 2023)
Conversation needs two people or more to be conducted. In doing conversation, diary is needed to help students to speak during conversation. Therefore, this study aimed to know the students’ perception on conversation diary, problems and solution. A mixed method was employed to achieve the research objectives. Thirty six students of English Education Study Program were the sample of this research. The instruments used were questionnaire and interview. The data were quantitatively and qualitatively analyzed by the researcher. The quantitative data were analyzed by using descriptive statistics with calculating mean scores and percentage, while the qualitative one used several stages namely reduction, displaying, and concluding the data. The results showed that majority students had a positive perspective on using diary in conversation class because based on the questionnaire, many students opted strongly agree and agree to all items. However, students faced several barriers namely speaking and psychological factors. In speaking skill, several students were lack of vocabulary, pronunciation, and grammar, while the psychological factors covered anxiety, self-confidence and motivation. Another finding displayed that improving motivation and joining public speaking can be alternative ways to deal with those barriers. In conclusion, conversation diary had benefits for students to support them in speaking. HIGHLIGHTS : Students had positive response towards the implementation of Conversation Diary in the classroom. Some students had problems in speaking, such as lack of speaking skill and psychological factors. Lecturer should provide speaking training to deal with the students' problems.